'Making Life Lively': Co-estrangement in live electroacoustic improvisation. Issue 1 (April 2021) - MacDonald, Alistair
Abstract : The use of live electronic processing to extend, modify or transform an acoustic musical instrument has its roots in the recording and broadcast technologies that were developed in the first few decades of the twentieth century. In the second half of the century these tools were adopted by composers and musicians in many musical genres and have become commonplace and in some musics, ubiquitous. The perceived musical relationship between instrument and its electronic 'other' has been discussed largely from the point of view of listener and composer. This paper focuses on the performers ' perspective through reflection on and discussion of the author's working methods in improvising duo contexts. The author suggests 'estrangement' as a term to describe and understand aspects of the performer's experience of live transformation and discusses how this estrangement might influence the relationship between musicians and the resulting musical interaction in improvisation, and finally offers 'co-estrangement' as a description of his shared experience in such improvising duos.